Evaluation of Oxidative Stress Markers in Chronic Periodontitis: A Comparative Study of Salivary and Serum Levels of 8-OHdG - Mouneshkumar (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Chronic periodontitis is an inflammatory disease characterized by the destruction of the periodontal ligament and alveolar bone. Oxidative stress, resulting from an imbalance between reactive oxygen species (ROS) and antioxidants, plays a significant role in its pathogenesis. 8-hydroxydeoxyguanosine (8-OHdG) is a widely recognized marker for oxidative DNA damage. This study aims to compare the levels of 8-OHdG in saliva and serum of chronic periodontitis patients and healthy controls to assess oxidative stress and explore the potential of salivary 8-OHdG as a non-invasive biomarker. Results: The mean age of participants was 45 ± 5 years, with equal gender distribution among cases and controls. Salivary 8-OHdG levels were significantly higher in the periodontitis group (7.85 ± 2.14 ng/mL) compared to controls (3.22 ± 1.05 ng/mL, p < 0.001). Serum 8-OHdG levels were also elevated in the periodontitis group (5.47 ± 1.68 ng/mL) versus controls (2.93 ± 0.98 ng/mL, p < 0.001). Conclusion: This study demonstrates that chronic periodontitis is associated with increased oxidative stress, as evidenced by elevated 8-OHdG levels in saliva and serum. Salivary 8-OHdG shows greater sensitivity and potential as a non-invasive biomarker for oxidative stress in periodontal disease. Further research is needed to validate these findings and explore therapeutic implications.